Pilot randomised controlled trial to improve hand hygiene through mindful moments. Issue 10 (20th February 2018) - Gilmartin, Heather; Saint, Sanjay; Rogers, Mary; Winter, Suzanne; Snyder, Ashley; Quinn, Martha; Chopra, Vineet
Abstract : Background: To evaluate the effectiveness of a brief mindfulness intervention on hand hygiene performance and mindful attention for inpatient physician teams. Design: A pilot, pre-test/post-test randomised controlled mixed methods trial. Setting: One academic medical centre in the USA. Participants: Four internal medicine physician teams consisting of one attending, one resident, two to three interns and up to four medical students. Intervention: A facilitated, group-based educational discussion on how mindfulness, as practised through mindful hand hygiene, may improve clinical care and practices in the hospital setting. Main outcomes and measures: The primary outcome was hand hygiene adherence (percentage) for each patient encounter. Other outcomes were observable mindful moments and mindful attention, measured using the Mindfulness Attention Awareness Scale, from baseline to post-intervention, and qualitative evaluation of the intervention. Results: For attending physicians, hand hygiene adherence increased 14.1% in the intervention group compared with a decrease of 5.7% in the controls (P=0.035). For residents, the comparable figures were 24.7% (intervention) versus 0.2% (control) (P=0.064). For interns, adherence increased 10.0% with the intervention versus 4.2% in the controls (P=0.007). For medical students, adherence improved more in the control group (4.7% intervention vs 7.7% controls; P=0.003). An increase in mindfulness behaviours was observed for the intervention group (3.7%) versus controls (0.9%) (P=0.021). Self-reported mindful attention did not change (P=0.865). Conclusions: A brief, education-based mindfulness intervention improved hand hygiene in attending physicians and residents, but not in medical students. The intervention was well-received, increased mindfulness practice, and appears to be a feasible way to introduce mindfulness in the clinical setting. Future work instructing clinicians in mindfulness to improve hand hygiene may prove valuable. Trial registration number: NCT03165799 ; Results.